Expectations and Experiences With Online Education During the COVID-19 Pandemic in University Students - Lobos, Karla; Cobo-Rendón, Rubia; Mella-Norambuena, Javier; Maldonado-Trapp, Alejandra; Fernández Branada, Carolyn; Bruna Jofré, Carola (Frontiers in Psychology, 2022)
Due to COVID-19, university students continued their academic training remotely. To assess the effects of emergency remote teaching (ERT), we evaluated the expectations and, subsequently, the experiences of university students about online education. Method: Simple prospective design. We assessed the expectations of 1904 students from different discipline areas (1106 females and 798 men; age M=21.56; SD =3.07) during the beginning of the first semester, March 2020 (T1), and their experiences at the end of the same academic period, September 2020 (T2). We used convenience non-probability sampling. Participants responded to the questionnaire on Expectations towards virtual education in higher education for students and the questionnaire on virtual education experiences in higher education. Results: Students' responses reflected low expectations regarding peer relationships and comparison with face-to-face education (T1). This perception was maintained during the evaluation of experiences (T2). Students reported positive experiences regarding online teaching and learning, online assessment, and their self-efficacy beliefs at T2. Statistically significant differences between measurements were found, with the expertise presenting higher averages than expectations. Furthermore, differences by gender were identified, reporting a positive change in the scores of women. In addition, results reflected differences according to the disciplinary area, showing Social Sciences and Medical and Health Sciences students a more significant size effect. Findings regarding the empirical evidence and the implications for future teaching scenarios in Higher Education are discussed.